Coexistence of Plasma Cell Dyscrasia with Prefibrotic Stage of Primary Myelofibrosis: A Case Report. (19th May 2011) - Tsirakis, George; Kanellou, Peggy; Kaparou, Maria; Passam, Andrew; Zampoulaki, Amalia; Stylianou, Kostas; Alexandrakis, Michael G.
Abstract : Introduction . Coexistence of myeloproliferative neoplasms with lymphoproliferative syndromes has been described in the past, whereas plasma cell dyscrasias seem to be the most common cases. Case Presentation . We present a case of a 59-year-old Caucasian female of Greek origin who presented with thrombocytosis. Clinical and laboratory investigation disclosed the presence of a smoldering myeloma with coexisting histological and molecular characteristics of primary myelofibrosis. The patient had the acquired point mutation V617F in the JAK2 gene but not the bcr-abl rearrangement and was treated for myelofibrosis with subsequent improvement of all haematological parameters without evidence of myelomatic evolution. Conclusion . We present the first case in the literature of a smoldering myeloma coexisting with primary myelofibrosis. The underlying pathogenetic mechanism could be either related to the presence of a pluripotent neoplastic stem cell capable to differentiate into both lymphoid and myeloid cells or be related to two separate nosologic entities.